June 1941 uprising in Panevėžys county in Krekenava township: events, participants, destinies - Jaskelevičius, Tadas (Genocidas ir rezistencija, 2020)
Preparation for the anti-Soviet uprising in Krekenava district. was active and well organized. There were frequent underground meetings and a plan for the liberation of Krekenava was prepared. The proactive rebels made ready on the afternoon of June 23, when two of their groups gathered in the forest near the town. The attack took place from two directions and did not take place without casualties on both sides. At least two rebels and several Soviet activists, militiamen and Red Army soldiers were killed in the battle. During the shooting Krekenava was reached by retreating Red Army units. The rebels had to abandon the town. On June24, 1941, the parish was occupied by the Germans. The rebels did not rush to disperse, believing that their work was not yet finished. They continued to carry out arrests of Soviet activists or those suspected in this way, and fought against the soldiers of the retreating Red Army. However, all of their actions were already controlled by the Germans and were only possible because they met the needs of the new occupier. A portion of the rebels contributed to the German-initiated holocaust. There is insufficient archival data to determine the exact number of contributors and their motivation. There is also a lack of data on the fact that some more organised anti-nazi movement would have been in place in the state. In 1944, when Lithuania was re-occupied by the Soviet Union, most of the rebels remained in their homes, of which about half (1944-1957) were arrested. They have all been criminalized and convicted. In contrast to the previous study in The Pine, the Krekenava rebels were given milder sentences, and no executions were carried out., After Stalin’s death, many rebels were released after the amnesty was introduced. Many of them returned to Lithuania.